2018
DOI: 10.3310/hta22190
|View full text |Cite
|
Sign up to set email alerts
|

Amaze: a double-blind, multicentre randomised controlled trial to investigate the clinical effectiveness and cost-effectiveness of adding an ablation device-based maze procedure as an adjunct to routine cardiac surgery for patients with pre-existing atrial fibrillation

Abstract: This project was funded by the NIHR Health Technology Assessment programme and will be published in full in ; Vol. 22, No. 19. See the NIHR Journals Library website for further project information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 69 publications
(104 reference statements)
0
18
0
Order By: Relevance
“…Studies of complex surgical interventions have reported changes in outcomes as a trial progresses [ 13 ]. Hence, studies may warrant investigation of a ‘period effect’, where patients recruited closer in time have more similar results due to protocol changes, learning effects or trial experience.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of complex surgical interventions have reported changes in outcomes as a trial progresses [ 13 ]. Hence, studies may warrant investigation of a ‘period effect’, where patients recruited closer in time have more similar results due to protocol changes, learning effects or trial experience.…”
Section: Discussionmentioning
confidence: 99%
“…The Amaze cardiac surgical trial assessed whether ablation during heart surgery returns the heart to normal sinus rhythm in patients with a documented history of rapid or irregular heart rhythm. 7 , 16 This multi-centre, Phase III, pragmatic RCT randomised 352 patients to ablation plus planned surgery, or planned surgery alone (control arm). The primary outcome was sinus rhythm restoration at one year post-surgery (binary outcome).…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] RCTs in surgery are increasingly used in a range of disease populations, including cancer, orthopaedic and cardiac patients. [5][6][7] These trials often adopt pragmatic designs to reflect the intervention as performed in clinical practice. During trial design, decisions are made about the inclusion and level of standardisation of each stage of the procedure, rather than imposing a strictly standardised protocol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preference-based PROs were used in six trials as primary outcomes, including five [21][22][23][24][25] that used the EQ-5D and one 26 that used the SF-6D. Seven trials used the qualityadjusted survival, including three 22 23 25 that used the EQ-5D and four [27][28][29][30] that used specific PROs for estimation. Patient satisfaction was used as the primary outcome Open access in two trials.…”
Section: Trial Characteristicsmentioning
confidence: 99%